Task-evoked pupillometry provides a window into the development of short-term memory capacity - Johnson, Elizabeth L.; Miller Singley, Alison T.; Peckham, Andrew D.; Johnson, Sheri L.; Bunge, Silvia A. (Frontiers in Psychology, 2014)
The capacity to keep multiple items in short-term memory (STM) improves over childhood and provides the foundation for the development of multiple cognitive abilities. The goal of this study was to measure the extent to which age differences in STM capacity are related to differences in task engagement during encoding. Children (n = 69, mean age = 10.5 years) and adults (n = 54, mean age = 27.5 years) performed two STM tasks: the forward digit span test from the Wechsler Intelligence Scale for Children (WISC) and a novel eyetracking digit span task designed to overload STM capacity. Building on prior research showing that task-evoked pupil dilation can be used as a real-time index of task engagement, we measured changes in pupil dilation while participants encoded long sequences of digits for subsequent recall. As expected, adults outperformed children on both STM tasks. We found similar patterns of pupil dilation while children and adults listened to the first six digits on our STM Overload task, after which the adults’ pupils continued to dilate and the children’s began to constrict, suggesting that the children had reached their cognitive limits and that they had begun to disengage attention from the task. Indeed, the point at which pupil dilation peaked at encoding was a significant predictor of WISC forward span, and this relationship held even after partialing out recall performance on the STM Overload task. These findings indicate that sustained task engagement at encoding is an important component of the development of STM.